Flow analysis of poultry feed in slender vertical silos with inverted cone insert (Research, Society and Development, 2020)
For an economical and safe design of vertical silos, factors such as the flow pattern that interfere with the distribution of loads in the silo, need to be carefully evaluated. Thus, the main objective of this research was to analyze the influence of the inverted cone insert, on the characteristics of the poultry feed flow in a vertical silo. The flow characterization experiment was conducted at the Seed Processing Laboratory, the flow properties, granulometry and moisture content determined at the Rural Construction and Ambience Laboratory - LACRA, both from the Federal University of Campina Grande, Campina Grande - PB. A longitudinally sectioned cylindrical silo with dimensions of 1.1m in height and 0.45m in diameter was used, representing a silo with an H / D ratio of 2.4, and a hopper 0.5 m high and 70º inclined to the horizontal, with 0.06 m discharge hole. The influence of the insert was evaluated in three different positions in relation to the discharge orifice: 0.35; 0.45 and 0.55 m. The feed presented difficulty in the flow, presenting the formation of cohesive arc, developing funnel flow, with several falls during its unloading, causing shocks in the silo structure, with the use of inverted cone insert, the formation of cohesive arc was not observed, changing the flow pattern of the stored product to mass.